(Invited) Conductive Bridging RAM (CBRAM): Then, Now, and Tomorrow. (19th August 2016) - Jameson, John R.; Blanchard, Philippe; Dinh, John; Gonzales, Nathan; Gopalakrishnan, Vasudevan; Guichet, Berenice; Hollmer, Shane; Hsu, Sue; Intrater, Gideon; Kamalanathan, Deepak; Kim, David; Koushan, Foroozan; et al.
Abstract : Conductive bridging RAM (CBRAM) is a resistive memory technology (RRAM) offering performance, power/energy, reliability, and cost advantages over incumbent nonvolatile memory technologies. The present article introduces the class of CBRAM in high-volume manufacturing today—subquantum CBRAM—and highlights similarities and differences between it and its predecessors. The materials requirements of subquantum CBRAM cells are described, and new insight into the switching mechanism is provided. Finally, its electrical characteristics are benchmarked, and its suitability for applications such as embedded memory, the Internet of Things (IoT), and radiation-tolerant electronics is summarized.